2010
DOI: 10.1103/physrevb.81.224431
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of small Cr clusters: Interplay between structure, magnetic order, and electron correlations

Abstract: The magnetic properties of small Cr N clusters ͑N Յ 6͒ are investigated in the framework of densityfunctional theory. The interplay between electron correlations, cluster structure, and magnetic order is quantified by performing fully spin-unrestricted calculations allowing for noncollinear spin arrangements within both the local-spin-density approximation ͑LSDA͒ and the generalized-gradient approximation ͑GGA͒. The possible transition or saddle-point states are identified by determining the vibrational freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
25
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 66 publications
(94 reference statements)
7
25
0
1
Order By: Relevance
“…A well-known example is the dimerization of Cr clusters. 31,32 By taking the optimal structures obtained in DFT, 9,30,33 SCTB calculations yield similar results. It is interesting to notice that for n d = 7, we found other NC solutions with higher energy.…”
Section: A Three-and Five-atom Clustersmentioning
confidence: 67%
See 2 more Smart Citations
“…A well-known example is the dimerization of Cr clusters. 31,32 By taking the optimal structures obtained in DFT, 9,30,33 SCTB calculations yield similar results. It is interesting to notice that for n d = 7, we found other NC solutions with higher energy.…”
Section: A Three-and Five-atom Clustersmentioning
confidence: 67%
“…It should be noticed, however, that noncollinearity is not the only mechanism for solving such magnetic frustration effects. Indeed, previous DFT calculations on Cr clusters 31,32 have shown that the actual ground state of Cr N magnetic corresponds to strongly dimerized structures with collinear local moments that are antiparallel along the short nearest-neighbors bonds (NN's) and eventually parallel along long bonds (next NN's). It is important to remark that the SCTB approach reproduces these trends very well.…”
Section: A Three-and Five-atom Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruiz-Diaz et al [6] have studied free Cr clusters using Vienna ab initio simulation package [21,22], they studied dimers, trimers, tetramers, pentamers and hexamer, using Local Spin Density Approximation of Vosko-Wilk-Nussair (LSDA-VWN) [23] and Generalized Gradient Approximation of Perdew-Burke-Ernzerhof (GGA-PBE) [17]. With the aim of comparing our results with those of Ruiz-Diaz et al, we show the results in Figs.…”
Section: Obtained Resultsmentioning
confidence: 75%
“…Its half-filled valence configuration leads to a large magnetic moment and strong interatomic bond [5]. Chromium clusters have been studied extensively in various configurations: free (pure [6] and doped with other atoms [7]) and deposited (in magnetic [8,9] and non-magnetic substrates [10,11]). Also experimental work was carried out with free [12] and deposited clusters on gold [13].…”
mentioning
confidence: 99%